A case of complete response following the administration of pembrolizumab and metastasectomy for lung and bone metastases of bladder cancer. Issue 2 (15th December 2021) - Nakasato, Takehiko; Inoue, Tatsuki; Kato, Ryosuke; Nakagami, Yoshihiro; Oshinomi, Kazuhiko; Maeda, Yoshiko; Morita, Jun; Shichijo, Takeshi; Yamochi, Toshiko; Fukagai, Takashi
Abstract : Introduction: Patients with metastatic urothelial carcinoma have poor prognosis and limited treatment options. Case presentation: The patient was a 60‐year‐old male with bladder cancer and multiple lung metastases. He underwent three courses of gemcitabine and cisplatin chemotherapy, despite left femoral bone metastases. Tumor resection and bone replacement surgery was performed. Following the administration of four courses of pembrolizumab, lung metastasis completely resolved. However, after nine courses, right femoral neck bone metastasis was observed; therefore, tumor resection and bone replacement surgery were repeated. Pathologically, PD‐L1 expression was low in lung biopsy tissue and bone metastases. Pembrolizumab treatment continued for up to 20 courses; cancer recurrence and adverse events were not observed upon follow‐up examination after 1 year. Conclusion: Patients responding well to systemic therapy may have resectable metastatic sites, and long‐term survival might be achieved with adjunctive metastasectomy. The effect of pembrolizumab was not associated with positive PD‐L1 expression.